Persepsi Siswa Terhadap Pelaksanaan Ekstrakurikuler Olahraga di SMAN 5 Kota Sukabumi - Muhammad Fikri Oktriansyah; Kurnia Eka Wijayanti; Riansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine students' perceptions of the implementation of extracurricular sports activities at SMAN 5 Sukabumi City. This study is important because it provides an overview of the quality of extracurricular sports implementation from the students' perspectives as a basis for evaluating and improving the quality of the program at the school. In addition, this study fills a research gap due to the limited research that specifically examines students' perceptions of the implementation of extracurricular sports at SMAN 5 Sukabumi City based on aspects of materials, facilities and infrastructure, and attention during the activity. The method used is a quantitative approach with a descriptive design. The research sample consisted of 116 students who are active in extracurricular sports activities selected using a total sampling technique. The research instrument was a validated Likert-scale closed questionnaire and covered three indicators: implementation of training, facilities and infrastructure, and student attention. Data were analyzed using descriptive statistics by calculating the average and percentage. The results showed that 79.90% of respondents' answers were included in the positive category, while 20.10% were included in the negative category. The three factors measured, namely materials, facilities and infrastructure, and attention, all showed positive perceptions from students. The conclusion of this study is that the implementation of extracurricular sports activities at SMAN 5 Kota Sukabumi was positively assessed by students and was able to support the development of sports skills, discipline, cooperation, and social interaction. The implications of this study are expected to provide evaluation material for schools in improving the quality of coaching, provision of facilities and infrastructure, and management of extracurricular sports programs on an ongoing basis. Keywords: Extracurricular Activity Implementation, Physical Education, Senior High School, Sports Extracurricular Activities, Students' Perception